2021
DOI: 10.1002/micr.30741
|View full text |Cite
|
Sign up to set email alerts
|

Lymphaticovenular anastomosis for lymph vessel injury in the pelvis and groin

Abstract: Background Lymphatic diseases due to lymph vessel injuries in the pelvis and groin require immediate clinical attention when conventional treatments fail. We aimed to clarify the effectiveness of and indications for lymphaticovenular anastomosis (LVA) to treat these lymphatic diseases. Methods We retrospectively evaluated six patients who underwent LVA for lymphatic diseases due to lymph vessel injuries in the pelvis and groin. Specific pathologies included groin lymphorrhea (N = 3), chylous ascites (N = 2), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Kobayashi et al suggested LVA to be a minimally invasive alternative to myocutaneous flaps for the treatment of wound complications caused by lymphedema and lymphorrhea after surgery for soft-tissue sarcomas in the adductor compartment of the thigh 16) . Regarding lower limb lympatic disorders, Katoda et al recommended LVA for the treatment of lymphatic diseases due to lymph vessel injuries in the pelvis and groin 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Kobayashi et al suggested LVA to be a minimally invasive alternative to myocutaneous flaps for the treatment of wound complications caused by lymphedema and lymphorrhea after surgery for soft-tissue sarcomas in the adductor compartment of the thigh 16) . Regarding lower limb lympatic disorders, Katoda et al recommended LVA for the treatment of lymphatic diseases due to lymph vessel injuries in the pelvis and groin 17) .…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7 However, as described by Giacalone et al and Kadota et al, such procedures are likely to induce subsequent lymphedema due to the obstruction of lymphatic vessels. 3,4 The best treatment would be to directly repair the damaged lymphatic vessels in the axilla by anastomosing them with intact lymphatic vessels. 2 However, because our patient had already undergone TE implantation and PMRT, it was expected to be difficult to find, dissect, and anastomose the lymphatic vessels through a chest skin incision.…”
Section: Discussionmentioning
confidence: 99%
“…After the postoperative day 2 puncture, no seroma accumulation was observed, which is compatible with previous reports noting the time required from LVA to resolution of lymphorrhea. 2,4 It is also possible that the lymphatic leakage was resolved due to radiotherapy, but recurrent seroma was observed after the puncture near the end of PMRT, suggesting again that LVA likely contributed to the resolution of lymphorrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 6 The best treatment for injured lymph vessels may be direct repair; however, it is difficult to find damaged lymph vessels in a previously treated and scarred wound. 8 In addition, lymphatic fluid is colorless and transparent, making intraoperative exact identification of lymphatic leak points difficult. So that treatment often fails, and additional treatments such as lymphaticovenular anastomosis are then often administered.…”
Section: Discussionmentioning
confidence: 99%